STRATEGI MANAJEMEN KURIKULUM DALAM PENINGKATAN KUALITAS PENDIDIKAN - Nuraeni, Anu; Rismayanti, Listia; Yoseptry, Ricky; Iriantara, Yosal; Rachmawati, Sisca; Ardiansyah, Yudah (STKIP PGRI Situbondo, 2025)
This study aims to analyze the curriculum management strategies implemented at SDN Puncak 2 in order to improve the quality of education. The research method used was a case study with a qualitative approach. Data were obtained through observation, in-depth interviews and documentation, which were then analyzed descriptively. The results show that SDN Puncak 2 implements several main strategies in curriculum management, including student needs-based planning, collaborative learning implementation and curriculum evaluation involving various stakeholders. These strategies are supported by the visionary leadership of the principal, the commitment of teachers in implementing learning, and the active involvement of parents and the community. The implementation of the strategy is proven to improve the quality of learning, marked by improved student learning outcomes and more structured learning activities. This study concludes that a directed and systematic curriculum management can be the key to success in improving the quality of education. The results of this study are expected to be a reference for other schools in managing the curriculum effectively and efficiently.